Selective Degradation of Styrene‐Related Plastics Catalyzed by Iron under Visible Light - Wang, Miao; Wen, Jinglan; Huang, Yahao; Hu, Peng (ChemSusChem, 2021)
Efficient degradation of plastics, the vital challenge for a sustainable future, stands in need of better chemical recycling procedures that help produce commercially valuable small molecules and redefine plastic waste as a rich source of chemical feedstock. However, the corresponding chemical recycling methods, while being generally restricted to polar polymers, need improvement. Particularly, degradation of chemically inert nonpolar polymers, the major constitutes of plastics, suffers from low selectivity and very harsh transformation conditions. Herein, an efficient method was developed for selective degradation of styrene‐related plastics under gentle conditions through multiple oxidation of sp3 C−H bonds and sp3 C−C bonds. The procedure was catalyzed with inexpensive iron salts under visible light, using oxygen as green oxidant. Furthermore, simple iron salts could be used to degrade plastics in the absence of solvent under natural conditions, highlighting the potential application of iron salts as additives for degradable plastics. Plastics degradation: An iron photocatalysis system improves the multiple C−H and C−C bond oxidative cleavage of substituted benzenes, applying oxygen as the terminal oxidant to produce benzoic acid selectively. The system is used to degrade styrene‐related plastics successfully, even under natural conditions without solvent.